(untitled) (Innovaciones Educativas, 2025)
This paper presents the main results of the research project Life stories focused on the praxis of teachers in the Costa Rican educational system: vocation, identity and professional challenges, whose purpose was to analyze the social conditions in which vocation was developed, the constitutive tensions of professional identity, and challenges and confrontation strategies. It was executed a qualitative study with in-depth interviews applied to four teachers from different education institutions in Costa Rica. Among results, it highlights that teachers’ vocation was developed from family references and professors role that served as models during their youth. Likewise, among the constitutive tensions of identity stands out the change in professional project to aspire for teaching after some vocational choices left beside, and the pressure of economic and social aspirations that affected in the decision of assuming teaching as an additional area or to complement it with other careers. The main challenges faced are associated with the incursion of technologies, the leader’s role that the teacher exercises and the empathy towards students. It is mainly concluded that the interviewed teachers life stories show professional trajectories marked by positive models that influenced the early vocational choice, besides family, community and institutional challenges that were faced as opportunities to strengthen the professional identity.